"We Don't Talk About That": Exploring Money Conversations of Black, Hispanic, and White Households. (25th April 2021) - White, Kenneth J.; McCoy, Megan; Watkins, Kimberly; Chen, XianYan; Koposko, Janet; Mizuta, Matthew
Abstract : Communication around finances is essential to relational satisfaction and the acquisition of financial skills. Nevertheless, people avoid financial discussions. Using data from the National Longitudinal Survey of Youth ( n  = 8, 006), this study explored how race/ethnicity relates to financial discussions through the lens of capital theory. Findings show that Black and Hispanic households had the lowest rates of financial discussions. When discussions did occur, the odds of them happening were higher with friends and lower with spouses/partners or family. Family and consumer science professionals can use the results to encourage financial communication in multiple types of relationships and households.